Business and Human Rights – Implementing the United Nations Guiding Principles on Business and Human Rights in Slovenia - Rozman, Til (LeXonomica, 2020)
Business enterprises have an independent responsibility to respect human rights. United Nations Guiding Principles on Business and Human Rights provides global standard for preventing and addressing the risk of adverse impacts on human rights linked to business activities. This paper builds on the finding that Republic of Slovenia is one of the few countries that have adopted national action plan on business and human rights. Paper further argues that state-owned enterprises should play key role in promoting, respecting and protecting human rights in business. Slovenian state has capital investments in a number of major companies, therefore, its responsibility for protection of human rights in business is even greater. After analyzing Slovenian national action plan on business and human rights, paper focuses on its implementation in the Slovenian business practices. It is argued that all Slovenian state-owned enterprises should explicitly commit to respect human rights in business and to prevent possible negative impacts on human rights as state-owned enterprises should lead by example. Furthermore, such commitment of the Slovenian state-owned enterprises would be in accordance with the concept corporate human rights due diligence which is expected to become mandatory in the EU in the near future.